ANALISIS KINERJA GABUNGAN PERKUMPULAN PETANI PEMAKAI AIR (GP3A) ARUNG RADEN DALAM PENINGKATAN PERTANIAN DI DAERAH IRIGASI PENGADANGAN KECAMATAN PRINGGASELA KABUPATEN LOMBOK TIMUR - MUHAMMAD NASRI (Journal of Agri Rinjani: Social Agricultural Economics - Faculty of Agriculture, UGR, 2022)
The purpose of this study was to determine the level of conformity of the performance of the Arung Raden Water-Using Farmers Association (GP3A) in the Pengadangan Irrigation Area, Pringgasela District and to determine the performance improvement strategy of the Arung Raden GP3A in the Pengadangan Irrigation Area, Pringgasela District in managing irrigation networks. Based on the results of the calculation of the level of conformity, it can be concluded that, in the organizational aspect, the indicator that has the highest level of conformity with a3 of 98.72% is an indicator that becomes the main priority and improves the performance of gp3a. Then on the irrigation aspect b1 of 98.63%, and the farming aspect there are 2 indicators that have the same suitability value and the highest is c1 of 89.61%, c2 of 89.61%. In the financial aspect, d2 is 97.33%, and the last is the role of the government e1 is 98.68%. The indicator that has the highest conformity value becomes the main priority. In the IPA Analysis (Performance Analysis Index), quadrant A is a quadrant that is a top priority that is very influential in the level of gp3a performance. To improve the performance of GP3A, the increase in rice production should not exceed 6 tons/ha.